1992
DOI: 10.1177/096120339200100204
|View full text |Cite
|
Sign up to set email alerts
|

A Phospholipid-β2-Glycoprotein I Complex Is an Antigen for Anticardiolipin Antibodies Occurring in Autoimmune Disease But Not with Infection

Abstract: Anticardiolipin antibodies (aCL) purified from patients with autoimmune disease have recently been shown to interact with a phospholipid-binding plasma protein, beta 2-glycoprotein I (beta 2-GPI). The aim of this study was to determine whether aCL purified from patients with infection also interact with beta 2-GPI. aCL purified from 23 patients with malaria, infectious mononucleosis, tuberculosis, hepatitis A or syphilis did not require the presence of beta 2-GPI to bind cardiolipin (CL). In contrast, aCL were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0
4

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(138 citation statements)
references
References 18 publications
6
128
0
4
Order By: Relevance
“…It is currently evident that the h 2 GPI ELISA has greater specificity and positive predictive value than the cardiolipin ELISA for the diagnosis of clinically significant APS [7,8]. These data confirmed previous experimental results on the role of h 2 GPI-dependent aPL in distinguishing between APS occurring in the setting of autoimmune diseases and the transient occurrence of aPL associated with infections [9]. In addition, it has been shown that most cases of clinically significant LA are associated with concomitant presence of anti-h 2 GPI antibodies in the sera of APS patients [10,11].…”
Section: Introductionsupporting
confidence: 82%
“…It is currently evident that the h 2 GPI ELISA has greater specificity and positive predictive value than the cardiolipin ELISA for the diagnosis of clinically significant APS [7,8]. These data confirmed previous experimental results on the role of h 2 GPI-dependent aPL in distinguishing between APS occurring in the setting of autoimmune diseases and the transient occurrence of aPL associated with infections [9]. In addition, it has been shown that most cases of clinically significant LA are associated with concomitant presence of anti-h 2 GPI antibodies in the sera of APS patients [10,11].…”
Section: Introductionsupporting
confidence: 82%
“…Recently, it was demonstrated that the binding of aCL from patients with SLE and with the APS to solid-phase CL was dependent on the presence of a serum cofactor, P,-GPI (13)(14)(15)(16). In contrast, aCL from patients with infectious diseases without thrombosis bound to CL without P,-GPI (13,14,17). Anticardiolipin antibodies that are dependent on P2-GPI might therefore be more important in the APS than aCL that are independent of P,-GPI, but the specificity and the epitope of these aCL have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Anticardiolipin antibodies have also been found in sera from patients with various infectious diseases, but aCL from these latter patients (who rarely had thrombosis) bound to CL without P,-GPI (13,14,17). P,-GPI consists of 326 amino acids and binds to anionic PLs (14,1&21).…”
mentioning
confidence: 99%
“…Autoimmune and drug-induced IgG and IgM aPL require ß 2 GPI for binding to phospholipids (PL). In contrast, the PL binding of aPL associated with syphilis, HIV, or other infection-induced antibodies is inhibited by ß 2 GPI (63,77). This divergence in the phospholipid binding by autoimmune and infectious aPL supports the proposal of a different origin for these two groups of aPL (61,78).…”
Section: Characteristics Of Antiphospholipid Antibodiesmentioning
confidence: 79%